CONSTRUCTIVE POLITICAL MYTH AS A KEY MEANS OF COUNTERACTING SIMULATION - Топалова, С.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article presents the authors conclusions based on a study main stages in the transformation of religious and mythological representations of the Japanese and their specific function in the political arena . Defined the essence of political myth , showed its key differences from the " mythological technological product," proved positive role of political myth and showed the main causes which contributed to the formation of a constructive political myth in Japan.